The Influence of Political Connections and Foreign Ownership on Tax Avoidance with Corporate Governance as a Moderating Variable - Pertiwi, Ni Pande Putu Intan Jati; Yuniarta, Gede Adi; Werastuti, Desak Nyoman Sri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of political connections and foreign ownership on tax avoidance, with corporate governance as a moderating variable. The research adopts a quantitative design, focusing on manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The sample was selected using purposive sampling, resulting in 36 companies that met the criteria. With three years of observation, a total of 108 financial reports were analyzed. Data collection was conducted through documentation studies, and the analysis employed Moderated Regression Analysis using panel data. The findings of the study indicate that both political connections and foreign ownership have a significant positive effect on tax avoidance. However, corporate governance does not moderate the relationship between these variables and tax avoidance. These results highlight the importance for manufacturing companies to establish more effective oversight and monitoring mechanisms to minimize tax avoidance practices.